2011
DOI: 10.1242/dev.063602
|View full text |Cite
|
Sign up to set email alerts
|

Generation of mice with functional inactivation oftalpid3, a gene first identified in chicken

Abstract: SUMMARYSpecification of digit number and identity is central to digit pattern in vertebrate limbs. The classical talpid 3 chicken mutant has many unpatterned digits together with defects in other regions, depending on hedgehog (Hh) signalling, and exhibits embryonic lethality. The talpid 3 chicken has a mutation in KIAA0586, which encodes a centrosomal protein required for the formation of primary cilia, which are sites of vertebrate Hh signalling. The highly conserved exons 11 and 12 of KIAA0586 are essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
107
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(116 citation statements)
references
References 52 publications
(53 reference statements)
7
107
1
1
Order By: Relevance
“…KIAA0586, the ortholog of chicken KIAA0586, was considered an excellent candidate gene given that its disruption in animal models causes defects, including polydactyly and abnormal dorsoventral patterning of the neural tube, attributed to abnormal hedgehog signaling. [8][9][10][11] The c.230C>G (p.Ser77*) variant (GenBank: NM_001244189.1) segregated with the expected patterns of autosomal-recessive inheritance in all available family members and is absent from dbSNP, the NHLBI Exome Sequencing Project (ESP) Exome Variant Server (EVS), the Exome Aggregation Consortium (ExAC) Browser, and 300 Lebanese control chromosomes. This homozygous nonsense variation is located in KIAA0586 exon 2, and mRNAs produced are predicted to be targeted for nonsense-mediated decay (NMD).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…KIAA0586, the ortholog of chicken KIAA0586, was considered an excellent candidate gene given that its disruption in animal models causes defects, including polydactyly and abnormal dorsoventral patterning of the neural tube, attributed to abnormal hedgehog signaling. [8][9][10][11] The c.230C>G (p.Ser77*) variant (GenBank: NM_001244189.1) segregated with the expected patterns of autosomal-recessive inheritance in all available family members and is absent from dbSNP, the NHLBI Exome Sequencing Project (ESP) Exome Variant Server (EVS), the Exome Aggregation Consortium (ExAC) Browser, and 300 Lebanese control chromosomes. This homozygous nonsense variation is located in KIAA0586 exon 2, and mRNAs produced are predicted to be targeted for nonsense-mediated decay (NMD).…”
mentioning
confidence: 99%
“…Thus, KIAA0586 mutant cells exhibit abnormal SHH responsiveness, suggesting that at least some of the defects in affected individuals with KIAA0586 variations might be secondary to abnormal SHH signaling, as observed in animal models. [8][9][10][11]17 In this study, using a targeted high-throughput sequencing strategy for candidate ciliary genes, we identified homozygous nonsense and splicing KIAA0586 mutations as responsible for lethal ciliopathies. This candidate-gene strategy previously succeeded in identifying ciliopathy genes, including TCTN3 (MIM: 613847), which is associated with Mohr-Majewski syndrome (OFD4 [MIM: 258860]).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the chicken embryo, Hensen's node is site of the first asymmetric gene expression, but this structure is thought to lack motile cilia. Chicken Talpid3 mutants with cilia defects develop normal LR asymmetry [78][79][80], indicating a cilia-independent mechanism is used for breaking symmetry. Indeed, cell-tracking experiments revealed that asymmetric cell movements around Hensen's node set up asymmetric signalling in the chicken embryo [81].…”
Section: (C) Laterality Cues For Cilia?mentioning
confidence: 99%
“…Fluorescent immunostaining was performed on cryosections of limb buds at stage 30 as described previously (Bangs et al, 2011). Primary antibodies used were anti-MafB (Santa Cruz; sc-10022), anti-Fos, anti-Jun and antimacrophage (Acris Antibodies; AM08143PU-N).…”
Section: Immunohistochemistrymentioning
confidence: 99%